Catholic Armenians in Brazil - Loureiro, Heitor [UNESP]; Scandolara, Daniel (Pontificia Univ Catolica Sao Paulo, Fac Teologia, 2023)
This paper aims to trace a brief history of Armenian Catholics in Brazil, highlighting religious and lay leaders who helped to create an Armenian Catholic community in the city of Sao Paulo. It starts from the plan to set up a Mission in the city to the difficult task to build a church for the small but very committed community of Armenian Catholics in the city. The challenges, the discussions, the events and also a problematization of the role of the Sao Gregorio Illuminator's Church nowadays are all aspects commented on throughout this paper. The aim is therefore to analyze the history but also to incite the dialogue regarding the Church's future.
Keywords: Armenians; Catholic; S?o Paulo; Armenian Catholics; S?o Greg?rio Iluminador